2021
DOI: 10.33555/jffn.v2i2.59
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Activities of Uli Banana Leaves on Oral Sugar Tolerance

Abstract: Banana has been widely cultivated. This study aimed to determine the antihyperglycemic activity of Uli banana leaves infusion. The antihyperglycemic activity was evaluated by oral glucose and sucrose tolerance test. A bolus of sugar was given after Uli banana leaves infusion and blood was sampled at 0, 15, 30, 60, 90 and 120 minutes for glucose analyses. The trapezoidal rule was used to determine the area under the curve (AUC) blood glucose. Infusion of Uli banana leaves 3.3 g/kg showed a significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…This condition indicates the mice were at the hyperglycemic level due to induction of sucrose. Increasing blood glucose levels in these mice were in accordance with several studies that indicated there was an increase blood glucose level in normal individuals after sugar administration orally (Gunawan-Puteri et al, 2020;Hendra et al, 2021). Other studies have reported an increase in glucose level of mice at 15 min after 4 g/kg sucrose administration (Poovitha et al, 2016;Gunawan-Puteri et al, 2018).…”
Section: Resultssupporting
confidence: 89%
“…This condition indicates the mice were at the hyperglycemic level due to induction of sucrose. Increasing blood glucose levels in these mice were in accordance with several studies that indicated there was an increase blood glucose level in normal individuals after sugar administration orally (Gunawan-Puteri et al, 2020;Hendra et al, 2021). Other studies have reported an increase in glucose level of mice at 15 min after 4 g/kg sucrose administration (Poovitha et al, 2016;Gunawan-Puteri et al, 2018).…”
Section: Resultssupporting
confidence: 89%